Pemahaman Ilmu Nahwu dan Tajwid “Waqaf dan Ibtida’” dalam Pembelajaran Al-Qur’an: Studi Kasus di Pondok Pesantren Ma’arif NU Metro - Nanda Fitriana Lukya; Subandi Subandi; Siti Roudhotul Jannah (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2023)
As a life guide for Muslims, the Qur'an is a must to study. Therefore learning the Qur'an has existed since the time of the Prophet and continues to this day. Especially in Islamic boarding schools, it is one of the things that is mandatory and must be studied by all students. In studying the Qur'an, other sciences are needed, for example, the science of Tajwid, Nahwu science and others as a support for studying it. The purpose of this research is to analyze how the Al-Qur'an is taught at the Ma'ariF NU Metro Islamic Boarding School, to analyze how the implementation of Nahwu and Tajwid knowledge in the waqaf and ibtida' in Al-Qur'an learning, and to analyze the supporting and inhibiting factors. This research uses a descriptive qualitative approach with a case study method on the implementation of Al-Qur'an learning at Ma'arif NU Metro Islamic boarding school. Researchers as the main instrument, with data collection techniques through in-depth interviews (with teacher and student components), observation and document study. All of the data is analyzed using an interactive model with the flow: data recording, data reduction, data presentation, data analysis and conclusions. The results of this study can be concluded as follows: First, in learning the Koran at Ma'arif Islamic boarding school using the bandongan and sorogan methods, and using tartil in reading the Koran. Second, all students are considered capable of implementing the knowledge of Tajweed in determining waqaf and ibtida', but not all students can implement Nahwu knowledge in determining waqaf and ibtida' in learning the Qur'an. Third, the factors supporting the implementation of nahwu and tajwid sciences in waqaf and ibtida', namely, the level of understanding and learning motivation is high, the teacher uses effective and efficient methods, the teacher always warns and corrects when students forget or make mistakes when reading the Qur'an. The inhibiting factors are low level of understanding and interest in learning, still unfamiliar with Nahwu knowledge, and limited hours of Al-Qur'an lessons.